1990
DOI: 10.1093/jnci/82.7.607
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of P-glycoprotein in Mammalian Tumor Cell Lines After Fractionated X Irradiation In Vitro

Abstract: We observed that in vitro exposure of mammalian tumor cells to fractionated x irradiation results in the expression of drug resistance. The cause of this resistance was investigated in a series of Chinese hamster ovary cell lines that had survived exposure to multiple lethal doses of radiation. These cell lines had increased levels of P-glycoprotein (Pgp), the multidrug-resistance-associated membrane glycoprotein. Consistent with the classic multidrug resistance phenotype, they exhibited cross-resistance to mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…On the other hand, no increase in the transcripts of mdr1a was detected (Granzotto et al, 2004). The increase in protein expression without an increase in mRNA was observed by other investigators who attributed this observation to an increased half-life of the ABC transporter protein or a post-translational effect of drugs (Hill et al, 1990;Westphal et al, 2000). However, another recent study demonstrated that in a tubular renal cell line, a 15-day treatment with rifampicin significantly increased the mRNA levels of P-gp, MRP1, MRP2, LRP, and CYP3A4 but an increase in protein was observed only for P-gp and MRP2 transporters (Magnarin et al, 2004).…”
Section: A Regulation Of Expression Of Atp-binding Cassette Transpormentioning
confidence: 73%
“…On the other hand, no increase in the transcripts of mdr1a was detected (Granzotto et al, 2004). The increase in protein expression without an increase in mRNA was observed by other investigators who attributed this observation to an increased half-life of the ABC transporter protein or a post-translational effect of drugs (Hill et al, 1990;Westphal et al, 2000). However, another recent study demonstrated that in a tubular renal cell line, a 15-day treatment with rifampicin significantly increased the mRNA levels of P-gp, MRP1, MRP2, LRP, and CYP3A4 but an increase in protein was observed only for P-gp and MRP2 transporters (Magnarin et al, 2004).…”
Section: A Regulation Of Expression Of Atp-binding Cassette Transpormentioning
confidence: 73%
“…Overexpression of the multidrug transporter Pgp and MDR protein (MRP1) has been extensively studied for its role in MDR (29). Pgp may be induced in cancer cells through exposure to irradiation (30) or cytotoxic agents such as paclitaxel, doxorubicin, or cisplatin (31). On average 40% and 50% of untreated breast cancers show expression of Pgp and MRP-1, respectively, and exposure to chemotherapy increases the expression of both proteins (29).…”
Section: Discussionmentioning
confidence: 99%
“…To examine in vitro antitumor efficacy of TAI-95, 11 breast cancer cell lines were screened and 9 of 11 tested cell lines were found to be highly sensitive to TAI-95, including MDA-MB-231, MDA-MB-468, T47D, Hs578T, ZR-75-1, MCF7, HCC1954, BT474, and ZR-75- 30 between 14.29 and 73.65 nmol/L. Notably, some of these cell lines which were resistant (GI 50 > 10 mmol/L) to other tested cytotoxic agents, including approved breast cancer drugs paclitaxel, doxorubicin, gemcitabine, and sorafenib, were very sensitive to TAI-95 (Table 1).…”
Section: Tai-95 Is Highly Potent In Breast Cancer Cell Linesmentioning
confidence: 99%
“…On the one hand, P-glycoprotein has been consistently found to be overexpressed in response to various kinds of stress, such as irradiation (Hill et al, 1990) or cytotoxic compounds not even expelled by this pump (Chaudhary and Roninson, 1993). In our camptothecin-resistant cell lines, there is a slight increase in P-glycoprotein expression at the first level of selection (probably responsible for the 3-fold resistance of this cell line to vincristine) and an important increase in this expression in the most resistant lines, C6 CPT50 and C6 CPT100 .…”
Section: Discussionmentioning
confidence: 99%